El desarrollo de la economía verde en el sector de alimentos en Colombia (2025)
The green economy in Colombia's food sector is key to mitigating environmental impact and promoting sustainability. The use of traditional practices and agrochemicals poses risks to natural resources and environmental health, while supply chain efficiency is a challenge. The adoption of sustainable agricultural practices, such as organic farming, along with development policies and incentives, seeks to reduce these impacts, generate green jobs, and improve resource efficiency. In Colombia, initiatives are being promoted that optimize supply chains and foster corporate social responsibility, integrating local communities.